Concentration of suspended solids in superintensive culture of the Pacific white shrimp Litopenaeus vannamei with biofloc technology (BFT): A review - Schveitzer, Rodrigo; Baccarat, Roberto Fábio Conway; Gaona, Carlos Augusto Prata [UNESP]; Wasielesky, Wilson; Arantes, Rafael (Wiley, 2024)
Microbial flocs (bioflocs) present in the water of intensive culture tanks are formed by a variety of microorganisms and other kinds of particulate organic matter, such as faeces and uneaten feed. During shrimp culture, biofloc concentrations increase. It has been reported that some level of control over biofloc levels, which can be quantified by the concentration of total suspended solids (TSS), is necessary for the adequate performance of the system. Some authors suggest that TSS concentrations below 600 mg L−1 are more appropriate for the superintensive culture of the Pacific white shrimp Litopenaeus vannamei in biofloc technology (BFT). However, subsequent research results contradict some of the arguments supporting the suggested solids limits, for example, the impact of increased solids on gill obstruction and subsequent shrimp survival. Recent studies have also shown the relationship between the control of solids and other important aspects of the system not considered so far, such as the control of opportunistic bacteria. Therefore, this topic seems worthy of revisiting, and it will be helpful to find new guidance toward understanding the levels of bioflocs that should be kept in L. vannamei culture tanks. In this review, we addressed the reasons that led to the establishment and limitations of the current biofloc levels for L. vannamei culture. The effects of maintaining low and high levels of bioflocs on both shrimp performance and the culture system are also analysed. Finally, perspectives on the management of biofloc levels are discussed, highlighting the advantages and disadvantages of each proposed strategy.
Keywords: biofloc concentrations; shrimp; solids levels; suspended particles; TSS